2010
DOI: 10.1097/mpg.0b013e3181bbf53d
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lactobacillus GG in Aboriginal Children With Acute Diarrhoeal Disease: A Randomised Clinical Trial

Abstract: Lactobacillus GG did not appear to enhance short-term recovery following acute diarrhoeal illness in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
0
41
0
4
Order By: Relevance
“…The conclusion is that L. rhamnosus GG had no impact on the total stool volume but did reduce the duration of diarrhea, particularly in the context of a rotavirus etiology. In contrast, four trials in children and infants with enterovirulent bacterium-or rotavirus-and enterovirulent bacterium-induced diarrhea showed no decrease in the daily number of stools or duration of diarrhea after treatment with L rhamnosus GG (313)(314)(315)(316). Multicenter and other RCTs in children and infants have shown that the administration of L. reuteri DSM 17938 (L. reuteri ATCC 55730) shortened the duration of acute diarrhea and lowered the diarrhea relapse rate (282,(317)(318)(319).…”
Section: Therapeutic Effects Against Various Forms Of Acute Diarrheamentioning
confidence: 97%
“…The conclusion is that L. rhamnosus GG had no impact on the total stool volume but did reduce the duration of diarrhea, particularly in the context of a rotavirus etiology. In contrast, four trials in children and infants with enterovirulent bacterium-or rotavirus-and enterovirulent bacterium-induced diarrhea showed no decrease in the daily number of stools or duration of diarrhea after treatment with L rhamnosus GG (313)(314)(315)(316). Multicenter and other RCTs in children and infants have shown that the administration of L. reuteri DSM 17938 (L. reuteri ATCC 55730) shortened the duration of acute diarrhea and lowered the diarrhea relapse rate (282,(317)(318)(319).…”
Section: Therapeutic Effects Against Various Forms Of Acute Diarrheamentioning
confidence: 97%
“…O Lactobacillus rhamnosus GG é associado a uma redução na duração e na gravidade da diarreia 65,66 . No entanto, estudos recentes com esse lactobacilo não relataram uma relação dose-eficácia ou foram negativos [67][68][69] . Várias metanálises [70][71][72] e uma revisão Cochrane 73 concluíram que, no tratamento de diarreia infecciosa aguda em crianças, os probióticos reduzem o número de fezes diarreicas e a duração da diarreia em aproximadamente 1 dia.…”
Section: Tratamento Com Pre E Probióticosunclassified
“…Only a few studies have directly compared probiotic products [60][61][62][63] or ranged doses [64,65]. The Cochrane review [21] found similar pooled estimates of efficacy for studies conducted in countries categorized by high or low mortality, nevertheless, a preponderance of negative studies [66,67,68,69,70,71] have been reported from resource-limited settings where infectious agents and the intestinal microbiota might be expected to be different from those of Western societies. Other little-explored influences on treatment include the role of prebiotic nutritional supplements, breastfeeding [26] or other dietary practices, the effects of accompanying or recent antibiotic treatment, the availability of clean water and adequate sanitation and other currently ill-defined influences on the resident microbiota.…”
Section: Probiotics For Acute Diarrhea Of Undetermined Etiologymentioning
confidence: 99%
“…Uncertainties aside, majority of reviewers and expert committees [65,66,67,68,69,70,71,72,73,74,75,76], including American Academy of Pediatrics [77] and European Society of Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) [78] have concluded that preparations containing probiotics (of the specific strains studied in these trials) both shorten the duration and reduce the severity of acute diarrhea in children.…”
Section: Probiotics For Acute Diarrhea Of Undetermined Etiologymentioning
confidence: 99%